2022
DOI: 10.3389/fonc.2022.952290
|View full text |Cite
|
Sign up to set email alerts
|

Pan-cancer genetic analysis of cuproptosis and copper metabolism-related gene set

Abstract: BackgroundA recent paper has revealed a novel cell death pathway, cuproptosis, a programmed cell death based on copper. This study aimed to evaluate the pan-cancer genomics and clinical association of cuproptosis and copper metabolism-related cell death genes, including SLC25A3, SLC25A37, SLC31A1, FDX1, DLAT, LIAS, ATP7A, ATP7B, COX17, SCO1, SCO2, COX11, and COX19.MethodsBy mining multi-omics profiling data, we performed a comprehensive and systematic characterization of cuproptosis genes across more than 9,00… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 58 publications
0
19
0
Order By: Relevance
“…As blood is a much more accessible clinical sample than tissues, the investigation of the plasma ORM2 levels in TNBC patients would be conducive to the development of ORM2 as a diagnostic and prognostic biomarker of TNBC. Bioinformatic analysis has been widely used to evaluate the prognostic value of genes [49][50][51][52][53][54][55], in this study, our bioinformatic analysis revealed that ORM2 was a potential prognostic biomarker for TNBC but not for non-TNBC.…”
Section: Discussionmentioning
confidence: 85%
“…As blood is a much more accessible clinical sample than tissues, the investigation of the plasma ORM2 levels in TNBC patients would be conducive to the development of ORM2 as a diagnostic and prognostic biomarker of TNBC. Bioinformatic analysis has been widely used to evaluate the prognostic value of genes [49][50][51][52][53][54][55], in this study, our bioinformatic analysis revealed that ORM2 was a potential prognostic biomarker for TNBC but not for non-TNBC.…”
Section: Discussionmentioning
confidence: 85%
“…Some researches have found that EGR2 is the target gene of miR-25 that can promote the proliferation of cancer cells, and knocking down EGR2 will promote the proliferation and spread of tumor tissues [ 58 ]. ATP7B is a type of copper effector transporter, which is a key protein in maintaining copper metabolism and copper homeostasis in cells, and is also associated with some cancer prognostic effects [ 59 ]. Cisplatin and carboplatin are common chemotherapy drugs, and ATP7B can mediate the resistance of cancer cells to platinum-based chemotherapy drugs, helping to alleviate the stress of cancer cells, resulting in poor benefits of traditional chemotherapy for patients [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…(GSEA: Hedgehog pathway, MAPK pathway,TP53 pathway, Autophagy pathway, Wnt pathway; GSVA: PI3K_AKT pathway,Wnt_BETA pathway,IL6_JAK pathway,Notch pathway,Oxidative pathway,TGF_BETA pathway) Given the impact of immune cell in ltration on the body's immune response in sepsis, where the systemic in ammatory response is the central disease mechanism, we investigated the expression levels of seven CRGs (XPO7, VTI1B, TMEM145, MTF1, ILIRN, FLOT2, CACNA1E) in the sepsis dataset in relation to immune cell correlation of in ltration abundance, along with 16 immune cells potentially regulated by cuproptosis. Numerous studies have proven that the degree of CRG expression correlates strongly with the condition of immune cell in ltration in the microenvironment of sick tissues in different forms of cancer [70][71][72][73] . Similarly, we discovered that CRGs have a role in altered immune in ltration of the organism in non-cancerous illnesses.…”
Section: Discussionmentioning
confidence: 99%